Five new scorpion species of genus Brachistosternus (Scorpiones: Bothriuridae) from the deserts of Chile and Peru, with comments about some poorly studied diagnostic characters of the genus - Ojanguren-Affilastro, Andrés A.; Pizarro-Araya, Jaime; Ochoa, José A. (Zootaxa, 2018)
Five new scorpion species of genus Brachistosternus of Chile and Peru are described. Brachistosternus gayi n. sp. is a high Andean species of north central Chile. Brachistosternus philippii n. sp. occurs near the coast of Antofagasta. Brachistosternus misti n. sp. occurs at intermediates altitudes of southern Peru. Brachistosternus contisuyu n. sp. occurs in Lomas formation in southern Peru. Brachistosternus anandrovestigia n. sp. occurs in coastal areas of southern Peru, and is the second known species of the genus without metasomal glands or androvestigia. Two diagnostic characters are discussed: the Internal Laminar Apophysis of the right hemispermatophore, and the sternum macrosetae.